Climatic drivers and temporal dynamics of sandstorms in the Hexi Corridor, China - Yanying Li; Xingwei Ma; Fucun Wang; Hongying Li; Xin Nie; Qifen Fu (Climate Services)
Daily data on sand-dust prevalence, precipitation, temperature, and wind speed from 13 national meteorological stations in wind and sand-prone areas of the Hexi Corridor were collected from 2005 to 2023, together with historical data from 1960 to 2020, to identify characteristic spatiotemporal variations in precipitation and temperature during 1–10 days before sand-dust events. The standardized precipitation evapotranspiration indices from January to December were also calculated. The influence of meteorological conditions at different time scales on the dust intensity in this region was then determined. It was found that (1) Sand abundance, the presence of desertified land, and the arid continental climate in the Hexi Corridor contributed significantly to the incidence of sandstorms in China. Due to its abundant sand, high temperatures, and large evaporation capacit-ies, Minqin showed the highest frequency of sandstorms. (2) The severe sandstorms and the high storm frequencies in the Hexi Corridor were found to be associated with warm and dry centers in the region, with the annual number of sandstorm days correlating positively with annual temperatures and negatively with precipitation (correlation coefficients of 0.58 and −0.29, respectively). (3) The wind thresholds of different dust intensities, precipitation, and temperature thresholds during the 1–10 days preceding sand-dust events, and their onset times were obtained,and the levels and regional distribution of drought in the Hexi Corridor during the preceding 1–12 months as well as the relationships among the parameters were assessed.